MODAL SOSIAL DALAM KELOMPOK PENGRAJIN ANYAMAN TALI STRAPPING TUNAS HARAPAN DI KECAMATAN TUALANG KABUPATEN SIAK - Wulandari, Stefi; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Strapping rope is a rope used by PT. Indah Kiat Pulp & Paper for binding pallets. Strapping rope waste generated by the company is increasing and usually the strapping rope is discarded by the company when it is no longer in use. However, this rope waste can be utilized by the community so as to produce crafts of economic value and then formed a woven strapping craft industry named group Tunas Harapan. This group of artisans has long existed and is still able to maintain its existence in modern times like today. This group of craftsmen is located in the Tualang Subdistrict, precisely in Tualang Village. The purpose of this study is to determine how the level of social capital elements that are owned by groups of artisans Tunas Harapan and to analyze the obstacles that exist in the group in maintaining its existence. The theory used in this study is the theory of social capital. This research is a quantitative research with descriptive type. The population and sample in this study were all workers or craftsmen of woven string strapping group Tunas Harapan by using census techniques, the researchers took the total population in the craft industry strapping group Tunas Harapan as many as 90 respondents. Data collection is done by field observations, interviews by preparing in advance a questionnaire or a list of questions and documentation. The analysis was carried out by group data processing in each indicator and cross tabulation. The results of this study can be concluded that the most powerful and dominant element of social capital in the Tunas Harapan group is the element of trust and norms. Whereas the most dominant obstacle in the Tunas Harapan group came from the respondent as a woven craftsman. Keywords: Social Capital, Tunas Harapan Woven Craftsmen Group